“Høit staaer Kunzen blandt Nutidens Sangcomponister ...” (1817): Bericht über Forschungsinitiativen zu Leben und Werk des Friedrich Ludwig Aemilius Kunzen (1761-1817) - Schwab, Heinrich W.; Harwell, Anna H. (Danish Yearbook of Musicology, 1995)
“Kunzen stands high among Comtemporary Song composers ... ” (1817): Report on the Research initiative concerning the life and works of Friedrich Ludwig Aemilius Kunzen (1761-I817) When the German-bom (1761 in Lübeck) Friedrich Ludwig Aemilius Kunzen, the HofkapelImeister of Copenhagen, died in 1817 the author of his obituary in the Leipziger Allgemeinen musikalischen Zeitung stated that one should "expect Kunzen's extensive biography rather soon" since he is held in high respect as both a man and artist. Despite this statement, such a monography has not yet appeared. The author, however, recenty has begun a research project that contains the folIowing individual details: 1. production of a documentary biography, 2. edition of letters to and from Kunzen, 3. creation of an annotated list of compositions, 4. edition of selected works, 5. an exhibition celebrating the 200th anniversary of Kunzen's return to Copenhagen in 1795 when he accepted "the position of his lifetime." Last but not least the project also includes 6. a close study of Kunzen's compositions, especially his not so seldom found "compositional individualism." Translated by Anna H Harwell